THEORY AND CALCULATION METHODS OF THREE-D RIGIDITY OF HYDRAULIC DRIVE MACHINES ELEMENTS - Alexander T. RYBAK; Alexander G. EFIMENKO (Advanced Engineering Research)
Calculation method for three-D rigidity coefficient of the elements of hydraulic drive machines is offered. Description of the stand for field research of the stiffness properties of the hydraulic systems pipelines, including three-D rigidity coefficient, is presented.